Successful Marketing Strategies for High-Tech Firms. - Viardot, Eric (Artech House, 2004)
This extensively revised third edition of the Artech House bestseller, Successful Marketing Strategies for High-Tech Firms, reflects the ruthless realities of the new high-tech marketplace where effective marketing strategy counts as much as the latest and greatest technology. The multitude of brand new material includes detailed case studies that teach the hard-learn lessons that have enabled such high-tech giants as eBay, Yahoo, IBM, Cisco, and Nokia to come out of the tech market meltdown stronger and more competitive. You learn how to develop innovative product offers that connect to actua.